KESADARAN DIGITAL MELALUI PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID - Hidayah, Yayuk; Hamonangan, Ranto Praja (Information Technology Education Department, 2024)
The research aims to find out how the development of android-based interactive media learning media in increasing students' digital awareness. The research process was carried out for five months, from August to December 2023. The research sample was students in the Department of Public Administration, Mekatronika Engineering and Automotive Engineering Education within the scope of the student population at Universitas Negeri Yogyakarta. The research method used is Research and Development (R&D) ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research findings reveal that the android-based interactive learning media that has been developed has high validity in terms of material, design, and interactivity. The results of student responses to products from android-based interactive media on the material of rights and obligations in learning Citizenship Education reached 122 or 81.33%. If included in the interval 81-100% with a very good category, this media is in a very good category from the aspect of attractiveness. The implication of the results of this study is the development of android-based interactive media in the general compulsory course of Civic Education, especially in Higher Education in accordance with future technological developments in the present and later. Through this study, researchers provide suggestions for developing android-based interactive learning media in the general compulsory course of Civic Education, especially in Higher Education.